The Forfeiture of Down Payments According to the Maqashid Syariah and Islamic Worldview - Ilham Aulia Fatani (Penerbit Hellow Pustaka, 2025)
In fulfilling their needs, humans are governed by laws established by Allah SWT, which regulate relationships between individuals and their Creator as well as among individuals themselves. Islam reminds humans not to harm one another, and exchanging goods within society is considered a fair means of meeting needs. The unified and codified regulations in fiqh mu’amalah cover various aspects of economic activity, including buying and selling (al-ba’i), which refers to the exchange of property based on mutual consent or the transfer of ownership with lawful compensation. According to Sulaimān al-Asyqar, buying and selling involves the exchange of property or benefits resulting in the transfer of ownership rights. One contemporary practice within this system is the use of a down payment or earnest money serving as a binding sign of agreement, where the buyer pays a portion of the price as a guarantee and is given a deadline to pay the remainder. This paper explains that earnest money is a payment or item given by a prospective buyer to a seller as confirmation that the transaction will proceed, and if the buyer cancels the agreement, the earnest money cannot be reclaimed.